National Institute of Standards And Technology (NINST) Method for Cyber Crime Using Forensic Data on Smartphone - Imam Zaenuddin; Yosua Novembrianto Simorangkir; Arman Syah Putra (IJISTECH (International Journal of Information System and Technology), 2022)
The background of this research is how to use the NIST method on crimes that use forensic data on smartphones, using the NIST method it will be known whether the method is the right one to use in case solving methods, especially in cybercrime cases. The method used in this study is to use the ethnic method which consists of the collection, examination, analysis, and reporting. With these 4 methods, it can be used to find out which data is used as crime data on smartphones that have been checked. The problem raised in this study is how to find out data that has been lost on a smartphone by using that data and using ethnic methods so that it can open the veil of crime in cyberspace. The purpose of this study is how to find the right data to be used as evidence, as evidence of crime using ethnic methods on smartphones.